HERITAGE TOURISM MARKETING IN TAMIL NADU: ISSUES AND DEVELOPMENTS - Sowmiya,; Dr. S. Subramanian, (The Bioscan, 2025)
Heritage tourism marketing plays a significant role in attracting tourists to heritage destinations. Tamil Nadu boasts an abundance of historical and archaeological sites. Well-planned marketing of these heritage destinations is a primary requirement to attract both foreign and domestic tourists. Several barriers can impede the successful marketing of heritage tourism Tamil Nadu. Poor and inadequate infrastructure facilities and management, non-availability of basic facilities in tourist places, lack of domestic and international airports, inadequate transport systems, and lack of requisite hotel accommodation. The conservation and protection system of heritage destinations is weak in our country, which plays a negative role in the marketing of these places. The present study is based on both primary and secondary data. The primary data has to be collected directly from the respondents, tourists, through a well-structured questionnaire and interview schedule. The secondary data was collected from the relevant articles published in different national and international journals, books, and pamphlets of the Tamil Nadu Tourism Development Corporation. The study invokes an outcome to develop knowledge and inhibit the importance of these heritage destinations among the youngsters, and modernization of these tourism products with an appropriate marketing mix upon the tourist requisition improves heritage tourism in Tamil Nadu. The development of new marketing strategies always brings in a new segment of people to visit these sites to make them live and flourish for more years.